Management of marine resources through a local governance perspective: Re-implementation of traditions for marine resource recovery on Easter Island. (November 2015) - Aburto, Jaime A.; Gaymer, Carlos F.; Haoa, Sonia; González, Lilian
Abstract: Easter Island (Rapa Nui) is one of the most isolated places in the world. The local Rapanui people have noticed an extreme decline in marine resources, which is due to the exploitation of these resources. Top-down regulations (e.g. fisherman and boat registrations and restrictions on catch-length and fishing season and location) implemented by the central fishery authorities located ∼4000 km from the island do not represent the cultural heritage and interests of the Rapanui people. According to the local people, one of the traditional ways to protect marine resources was the taboo (or tapu in Rapa Nui) that regulated the fish harvest. Key informants were interviewed to assess what they knew about the tapu in fisheries and so that the feasibility of its implementation could be assessed based on current local conditions. The tapu that had the greatest potential impact on regulating open water resources, especially tuna, was the traditional belief that consumption of open-water fish during winter months would cause asthma. According to the interviewees, the real reason for this tapu was to protect the fish during its reproductive period, and the asthma threat was only a way to enforce the restriction. At present, tapu is not respected because of the high economic activity related to the tourism that demands fish like tuna all year. Even though many Rapanui people agree that tapu re-implementation would be the best alternative to recover marine resources, people also think it is difficult to implement under modern conditions. We propose to promote a participatory process for development of a local governance structure that will use local traditions and beliefs, including tapu, to support the local decision-making process for reverting the decline of marine resources. Highlights: The perception of local people (Rapanui) is that marine resources are declining. Central fisheries regulations do not fit with the Polynesian culture of Rapanui. Implementation of ancient tapu for resources recovery was suggested by the Rapanui. In the past, tapu did not allow consumption of open water fishes, such as tuna. In the present, there is not a governance scenario to re-implementing tapu.